Can Traditional Treatment Modalities Still be a Benchmark for Managing Systemic Lupus Erythematosus? - Rashmi Vikrant Sane; Vikrant Dilip Sane; Shams-; Vivek Sunil Nair; Nishita Bhosale (Wolters Kluwer Medknow Publications, 2024)
Systemic lupus erythematosus (SLE) is a multisystem disorder with a variable clinical presentation, showing multiple active clinical manifestations, and an alternating course of flares and cutbacks of the disease itself and or treatments received. Here we present a case report of Chronic Cutaneous Lupus erythematosus seen in a 28-year-old male patient at the vermilion border of the lip, chest, and flexor surfaces of arms managed effectively by the traditional treatment modalities like topical and systemic steroids. Modern alternatives like B-cell target therapy, T-cell target therapy, and Immunoregulatory molecule-targeting therapies with the help of Interferon-alpha inhibitors appear to be safe and effective but are still in clinical trials due to some co-morbidities. Follow-up for 1 year showed no signs of recurrence and had a good prognosis.